Analisis Berpikir Kritis Siswa SMP dalam Memecahkan Masalah Segitiga Berbantuan Geogebra - Defi Imamatus Sholikha; Tatag Yuli Eko Siswono (MATHEdunesa, 2023)
Critical thinking is an important skill in making life changes for every individual. The importance of critical thinking causes the need to be developed since school. Learning in schools today needs to be linked to technology because it can improve students' critical thinking, one of which is GeoGebra. However, nowadays in the learning process not many or even no one has implemented technology-assisted learning, so it is necessary to implement technology-assisted learning, especially GeoGebra to help improve students' critical thinking. This research is a qualitative research using case studies. The purpose of this study was to analyze the critical thinking of students who were successful, less successful and unsuccessful in solving geogebra-assisted triangle problems. The subjects of this research were 3 students who fulfilled this research category. The results showed that (1) students with the category of successfully solving triangle problems with the help of Geogebra could fulfill all indicators of critical thinking well at each stage of solving triangle problems. (2) students in the less successful category of solving triangle problems with the help of Geogebra, can only fulfill 3 indicators of critical thinking skills, namely interpretation, analysis, and evaluation. (3) students in the category of not being successful in solving triangle problems with the help of Geogebra, can only fulfill 1 indicator of critical thinking skills well, namely interpretation.